SIMULATION OF PLACEMENT FOR FOAM INLET INJECTOR POSITION ON FIREFIGHTER JET NOZZLE - Hadi Sutrisno, Himawan; Kusumohadi, Catur Setyawan; Yudistira, Nopel Syahdan (Indonesian Physical Review, 2025)
Water is a widely used and effective fire-extinguishing medium, but its effectiveness diminishes at high temperatures. By disrupting the oxygen chain in the fire triangle, Foam media can enhance suppression performance. This study simulates the impact of foam injector placement on the effectiveness of jet nozzles in fire extinguishers. Simulations were conducted with foam injectors positioned at the nozzle's inlet, middle, and outlet. Results indicate that placing the foam injector at the outlet provides optimal spray velocity, pressure, and extinguishing performance. These findings highlight the importance of injector placement in improving fire suppression efficiency for liquid-based extinguishing systems.